Spiritual Healing and Self-Discovery in Independent Umrah: A Study of the Perceptions of Young Z Generation Pilgrims - Adi Irawan (Jurnal Iman dan Spiritualitas, 2026)
This study aims to analyze the spiritual experiences, motivations, and self-transformation of young Z generation pilgrims who performed the Umrah independently in 2025. A qualitative approach was used with in-depth interviews with eight pilgrims, two mutawifs, and one Umrah travel agency manager. The results show that the decision to perform the Umrah independently is driven by spiritual needs, self-discovery, the need for flexibility, and the influence of social media. The most dominant emotional experiences arise during the moment of seeing the Kaaba and performing the tawaf, which gives rise to feelings of emotion, amazement, and a strong existential awareness. In addition to producing inner peace during the pilgrimage, the independent Umrah also encourages behavioral changes after returning home, especially in worship discipline, emotional management, and a more spiritual orientation. Travel challenges such as language barriers, navigation, and logistics actually strengthen the independence and problem-solving abilities of young pilgrims. This study concludes that the independent Umrah is a form of contemporary religiosity for Z generation that prioritizes authentic experiences, freedom, and self-development. These findings imply the need for Umrah service providers to adapt their approaches to suit the characteristics and needs of the increasingly independent and experience-oriented younger generation.